Research on Covid-19 from Biophysical Perspective - Lamichhane, Tika Ram; Ghimire, Madhav Prasad (Tribhuvan University Journal, 2020)
In this report, we discuss the current aspect of biophysics which is an essential field to investigate the structural and related properties of SARS-CoV-2 components, possible drugs likeliness and their interactions, and mathematical as well as clinical data modeling. We have emphasized that a mathematical model generates the sigmoid logistic equation that predicts the total corona virus cases and deaths in a model country with population averaged from the most vulnerable countries, such as India or USA, where the COVID-19 cases are still spiking up and from the countries which are on the process of recovering from the current pandemic. Further, the current status of COVID-19 research has been explained to understand its impacts taking Nepal as the reference country having low-income. In particular, focus is on biophysical study on structural analysis of novel coronavirus main protease which is found to influence the radial distributions of H-bonding atom pairs when interacting with the inhibitors N3. Explorations of the variations of physical parameters are found to be important in drug selective mechanism against COVID-19 infections.